2022
DOI: 10.1111/hae.14638
|View full text |Cite
|
Sign up to set email alerts
|

Management of haemophilia A with inhibitors: A regional cross‐talk

Abstract: Introduction The development of inhibitors with factor VIII (FVIII) replacement therapy is one of the most common and challenging complications of haemophilia A (HA) treatment, jeopardising treatment efficacy and predisposing patients to high risks of morbidity and mortality. The management of patients with inhibitors is particularly challenging in countries where resources are limited. Aim To provide a comprehensive summary of the management of HA with inhibitors while focusing on differences in practice betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 102 publications
0
9
1
Order By: Relevance
“…However, the COVID-19 pandemic and difficult access to transportation resulted in a low number of patients participating in our study. The prevalence of FVIII inhibitors among patients with severe HA in our study (25/219, 12%) was considered relatively low compared to that in studies from Western countries conducted by the Research of Determinants of Inhibitor Development (PedNet study group) and the UK Hemophilia Centre Doctors' Organization (UKHCDO), with the most reported prevalence ranging between 20% and 30% of severe HA [9][10][11][12]. This result may be owing to the use of low-dose FVIII plasma-derived therapy in Indonesia.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…However, the COVID-19 pandemic and difficult access to transportation resulted in a low number of patients participating in our study. The prevalence of FVIII inhibitors among patients with severe HA in our study (25/219, 12%) was considered relatively low compared to that in studies from Western countries conducted by the Research of Determinants of Inhibitor Development (PedNet study group) and the UK Hemophilia Centre Doctors' Organization (UKHCDO), with the most reported prevalence ranging between 20% and 30% of severe HA [9][10][11][12]. This result may be owing to the use of low-dose FVIII plasma-derived therapy in Indonesia.…”
Section: Discussioncontrasting
confidence: 61%
“…In India, one study on patients with bleeding disorders also reported a slightly lower prevalence of inhibitors, which occurred in 6.1% of 1,285 patients with HA. This small number also reflects the undertreatment of patients with hemophilia, where only infrequent episodic treatment is applied, thus rarely resulting in peak treatment moments that subsequently lead to inhibitor development, especially in young patients [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the patients on emicizumab prophylaxis gain additional QALYs and it costs the health system lesser than the existing on-demand bypassing agent treatment (i.e., less costly and more effective). Severe Haemophilia A patients with inhibitors are currently treated with on-demand bypassing agents (recombinant factor VIIa/APCC) across various public health hospitals of India [ 23 ]. Prophylactic emicizumab therapy, in addition to being a cost-saving intervention, has several other advantages such as prevention or reduction in the number of bleeding episodes, ease of compliance (given the once or twice monthly prophylactic regimen), reduction in healthcare system costs (subcutaneous administration of agent) and better quality of life for the patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although new hemostatic agents, bypassing the need for FVIII replacement, are now available, spontaneous bleeds may still occur in individuals under prophylaxis non-FVIII therapies, leading to the need for FVIII injections ( 3 , 4 ). However, the development of neutralizing anti-FVIII antibodies, known as “inhibitors”, can complicate or preclude effective FVIII replacement therapy ( 5 ). The immunological mechanisms behind the immunogenicity of pro-coagulant FVIII remain unclear ( 6 ).…”
Section: Introductionmentioning
confidence: 99%